High energy (150 MeV) Fe11+ ion beam induced modifications of physico-chemical and photoluminescence properties of high-k dielectric nanocrystalline zirconium oxide thin films. Issue 15 (15th October 2019) - Chauhan, Vishnu; Gupta, Rashi; Kumar, V.; Ram, J.; Singh, F.; Prasad, M.; Kumar, S.; Ojha, S.; Alvi, P.A.; Mehra, R.; Kumar, Rajesh
Abstract: This work presents the influence of dominated electronic energy loss over nuclear energy loss induced by swift heavy ion (SHI) irradiation on the physico-chemical, optical and other properties of RF grown zirconium oxide (ZrO2 ) thin films. For this purpose, thin films of ZrO2 grown on glass substrate were irradiated by 150 MeV Fe 11+ ions with a range of fluence from 2E12 to 5E13 ions/cm 2 to understand the mechanism of induced modifications and defects generation. The XRD results confirmed that the virgin and irradiated ZrO2 thin films were crystalline in nature with monoclinic and tetragonal structure. The crystallite size varied from 19.93 nm to 46.43 nm with varying ion fluence. Strain, dislocation density and stacking fault were used to investigate the changes in structural parameters. Tauc's plot method was employed for the quantitative evaluation of optical energy band gap (Eg ) that exist in the range of 4.45–4.62 eV. The transmittance (%) of the virgin and Fe 11+ ions irradiated samples was determined in the range of 35.69–66.09% using UV–Vis. spectroscopy. Further, the refractive index was determined using different methods significantly depends on the optical band gap. The broad PL emission peaks were obtained at 375 nm and 440 nm with the excitation wavelength (λex .) of 300 nm. The variation in PL intensity with increasing ion fluence was attributed to the creation or annihilation of primary or complex defects. FTIR spectroscopy was employed for the analysis of chemical modifications in vibrational bonds of samples and the band obtained 660 cm −1 was assigned to the asymmetrically coupled Zr–O–Zr stretching which presents the strong vibration in samples. The band intensity increased up to the fluence 5E12 ions/cm 2 and decreased at a higher fluence of 1E13 ions/cm 2 . Rutherford backscattering spectroscopy technique was used to determine the thickness (165 nm) of the samples.